Woody Species Composition, Structure and Diversity of Trees-Based Agroforestry System in the Mid-Highlands, Konawe Regency, Southeast Sulawesi Province, Indonesia - Agus Setiawan; Nur Arafah (Journal of Global Innovations in Agricultural Sciences)
This study aims to examine woody species composition, structure, and diversity of Tree-based agroforestry systems in the mid-highlands, Konawe Regency, Southeast Sulawesi Province, Indonesia. Data was collected in each observation plot in the agroforestry patterns. The total number of observation plots was thirty-three. The plot sizes for saplings 5m x 5m, poles 10m x 10m, and trees 20m x 20m. The results found there were 31 plant species composition belonging to 18 families. Plant species at the tree level 73%, herbaceous 10% and shrubs 17%, native endemic species 74%, and introduced 26%. A total of 77% of plant species were planted and 23% of species grew wild. The structures tree level vegetation with the highest importance value index (IVI) was the Tectona grandis species with IVI 144.9, the pole layers were Tectona grandis with IVI 126.7, and the sapling layers were Theobroma cacao with IVI 94.0. While the structures tree level vegetation with the lowest IVI was Artocarpus heterophyllus with IVI 13.4, the pole layers were Mangifera indica with IVI 13.2, and the sapling layers were Syzygium polyanthum and Citrus aurantiifolia with IVI 15.5. The highest species diversity index in the agroforestry of community forest was 1.7. Species richness index (M') and evenness index (E') were evenly distributed all in the agroforestry patterns with moderate criteria. The findings research show that agroforestry systems in the study area are diverse, with the different wood species compositions and structures. Keywords: Agroforestry, composition, community forest, konawe regency, species diversity, structure, southeast Sulawesi, vegetation.